IFN-GAMMA AND IL-2 SECRETION AFTER ESAT-6-CFP-10 (EC-610) FUSION ANTIGEN STIMULATION FROM PATIENTS WITH ACTIVE LUNG TUBERCULOSIS AND LATENT LUNG TUBERCULOSIS - Darwin, Bastian; Kurniati, Nova; Rahadiyanto, Kemas Ya'kub; Saleh, Mgs Irsan; Tanoehardjo, Francisca Srioetami; Nugraha, Jusak; Salim, Eddy Mart (Biomedical Journal of Indonesia, 2020)
The Secretion of IFN-Gamma and IL-2 After ESAT-6-CFP-10 Fusion Antigen Stimulation in Active and Latent TB Patients. This study held to discover how immune responses work and to know the pathogenesis of active TB and latent TB patients. This study used PBMC to stimulate T Cells with ESAT-6 and CFP-10 antigen fusion, and measure the level of IFN-gamma and IL-2 with ELISA antibody sandwich (U-Cytech). 16 ml of blood were drawn to 5 tubes. ESAT-6 CFP-20 inducted one tube with QuantiFERON for IFN-gamma assay. The other four tubes were PBMC isolated using Ficoll-Paque, and pre-incubated with stimulation of ESAT-6 CFP-10 fusion antigen for 24-72 hours at 370 C and measured using T-Spot and ELISA reader. We got from this study that there are no significant differences in IFN-gamma levels for both groups with active TB and latent TB. Measurement of IL-2 levels showed significant differences between the two group.